Tindakan Penyidik Dalam Mengamankan (TKP) DanKeberhasilan Penyidikan(Study Kasus Di Polsek Colomadu) - Saifudin, Khanif, Muchammad Iksan, SH.MH (2017)
This study aims to determine the procedures to implement the security and processing the crime scene in the success of the investigation by the police investigators as well as an inhibiting factor in securing the implementation of the crime and its solution. The method used is the juridical empirical legal research methods. This type of research is descriptive law research. From the research procedures of securing and processing the crime scene by police investigators based on the two-Law No. 2 of 2002 on the Indonesian National Police and the Police Regulation No. 14 Year 2012 on the Crime Investigation Management. The conclusion of this study is compatibility between guidelines for the implementation of security and processing the crime scene with the implementation of security and processing the crime scene conducted by Colomadu police investigators sector. Barriers arising from limit the ability of investigators and the destruction of the conditions of the crime.